SUBHDIP: process variations tolerant subthreshold Darlington pair‐based NBTI sensor circuit. Issue 3 (3rd December 2018) - Shah, Ambika Prasad; Yadav, Nandakishor; Beohar, Ankur; Vishvakarma, Santosh K.
Abstract : Aggressive technology scaling has inevitably led to reliability becomes a major concern for modern high‐speed and high‐performance integrated circuits. The major reliability concerns in nanoscale very‐large‐scale integration design are the time‐dependent negative bias temperature instability (NBTI) degradation. Owing to increasing vertical oxide field and higher operating temperature, the threshold voltage of P‐channel MOS transistors increases with time under NBTI. This study presents a novel subthreshold Darlington pair‐based NBTI degradation sensor under the stress conditions. The proposed sensor provides the high degree of linearity and sensitivity under subthreshold conditions. The Darlington pair used in the circuit provides the stability and the high‐input impedance of the circuit makes it less affected by the process variations. Owing to high sensitivity, the proposed sensor is best suited for sensing of temperature variation, process variation, and temporal degradation during measurement. The sensitivity of the proposed sensor at room temperature is 0.239 mV/nA under subthreshold conditions. The proposed sensor is less affected by the process variation and has the maximum deviation of 0.0011 mV at standby leakage current of 30 nA.